1985
DOI: 10.1073/pnas.82.13.4389
|View full text |Cite
|
Sign up to set email alerts
|

Faithful cell-cycle regulation of a recombinant mouse histone H4 gene is controlled by sequences in the 3'-terminal part of the gene.

Abstract: We have analyzed the expression of endogenous histone H4 genes and of a newly introduced H4 gene in 21-Tb cells, a mouse mastocytoma cell-cycle mutant. Endogenous H4 mRNAs were less abundant by a factor of 120-180 in Gl-arrested than in exponentially multiplying cells. However, H4 transcription rates were only decreased by a factor of 3 under these conditions, as determined by in vitro elongation of nascent transcripts. This indicates that post-transcriptional control of histone mRNA levels is important, in ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
66
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(69 citation statements)
references
References 41 publications
3
66
0
Order By: Relevance
“…This sequence is particularly noteworthy in light of the extremely high A+T content of noncoding regions in D. discoideum mRNAs (67). More definitive evidence for the importance of 5'-and 3'-UT regions has come from recent experiments in which these regions have been deleted, replaced, or transferred, resulting in substantial changes in the decay rates of individual mRNAs (22,42,53,64,74,76). The most well-characterized of the UT elements are the 3' AU-rich sequences associated with the GM-CSF mRNA (and other lymphokine and protooncogene mRNAs [12,50,74]) and the 3' stem-loop structure associated with the replication-dependent histone mRNAs (21,68 Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This sequence is particularly noteworthy in light of the extremely high A+T content of noncoding regions in D. discoideum mRNAs (67). More definitive evidence for the importance of 5'-and 3'-UT regions has come from recent experiments in which these regions have been deleted, replaced, or transferred, resulting in substantial changes in the decay rates of individual mRNAs (22,42,53,64,74,76). The most well-characterized of the UT elements are the 3' AU-rich sequences associated with the GM-CSF mRNA (and other lymphokine and protooncogene mRNAs [12,50,74]) and the 3' stem-loop structure associated with the replication-dependent histone mRNAs (21,68 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that these complex decay kinetics reflect the sum of the decay rates of individual mRNAs (e.g., in D. discoideum, the most stable mRNAs have half-lives of approximately 10 h and the least stable mRNAs have half-lives which are approximately 10-fold shorter). It has been suggested that such large differences in the stability of individual mRNAs could be accounted for by differences in their respective sizes (39,52,58,63,78,81), poly(A) tail lengths (8,28,56,91), ribosome loading (1,26,33,41,45), or 5'-and 3'-untranslated (UT) sequences (42,53,64,69,74,76,89). To test the validity of these hypotheses, we have identified cloned cDNAs which encode mRNAs that are representative of the stability extremes in D. discoideum and have initiated a characterization of the properties of the respective mRNAs.…”
mentioning
confidence: 99%
“…So far, the information on these points is based on in vivo experiments with either frog oocytes (Birchmeier et al, 1982(Birchmeier et al, , 1983(Birchmeier et al, , 1984Stunnenberg and Birnstiel, 1982;Galli et al, 1983), or tissue culture cells (Luscher et al, 1985) as test sytems. The discovery of the U7 RNA as an essential component of the processing machinery derives from one such experimental design.…”
Section: Discussionmentioning
confidence: 99%
“…1B). The stem-loop is essential for proper cell cycle regulation and is the site at which mRNA degradation begins (4,14,29,31,39,47,56,57,65,68,75). It is also a binding site for a unique stemloop binding protein (40,46,72,73,76).…”
mentioning
confidence: 99%
“…Specificity is achieved primarily via the unique 3Ј-terminal structure of histone mRNA. The 3Ј terminus lacks poly(A) and contains a 6-bp stem and 4-base loop (29,31,45) (see Fig. 1B).…”
mentioning
confidence: 99%